Implicit attitudes in L2 motivation research: The case of learning English and Mandarin in Hong Kong - Boo, Peizhen/Zann (2021)
The field’s current understanding of L2 motivation is largely reliant on explicit self- reports (e.g. questionnaires and interviews). While such means have provided the L2 motivation field with a wealth of understanding, the underlying assumptions are that such attitudes take place in a conscious manner and that such representations are adequate. Recent developments have discussed these limitations and have called for a more in-depth and holistic understanding of the motivational psyche of L2 learners (e.g. Al-Hoorie, 2016a; Dörnyei, 2020). This thesis seeks to address this research lacuna by arguing for the inclusion of an implicit dimension into L2 motivation research, using the case of Hong Kong as an illustration.